THE EFFECT OF MOVIE SYNOPSIS ON STUDENTS’ VOCABULARY MASTERY OF THE FIRST GRADE STUDENTS AT MTSN 2 BENGKULU - ZASRIANITA, FERA; PUTRI, MELU SUDARMI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This research aims to know the effect of using movie synopsis on students' vocabulary mastery in the first-grade students of MTsN 2 Kota Bengkulu. The population of this research is seven classes of the first-grade students of MTsN 2 Kota Bengkulu; the total number is 301 students. The sample was taken by class VIIB, an experimental class with 30 students, and class VIIA, a control class with 30 students. The instrument of the research used a vocabulary test. The data was evaluated and analyzed to determine the effect using the T-test Formula. The result means that there are differences between both classes in the effect of movies synopsis on students' vocabulary mastery. In other words, the experimental class's vocabulary increased more than the control class. The mean score of the pre-test result of the experimental class was 58,56, the mean score of the control class was 59,86, the mean score of the post-test result of the experimental class was 76,63, and the control class was 61,90. The gain of pre-test and post-test of the experimental class was 18.07, and the gain of pre-test and post-test of the control class was 2.04. It means movies' synopsis as education media was influential in developing students' vocabulary mastery. The researchers suggest that teachers use the synopsis of the movie as one of the techniques in teaching vocabulary, so the teacher can motivate the students to develop their vocabulary mastery and contribute to developing the teaching and learning English process, especially in teaching English vocabulary.